2022
DOI: 10.1101/2022.07.24.501306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microcephaly-associated WDR62 mutations hamper Golgi apparatus-to-spindle pole shuttling in human neural progenitors

Abstract: WDR62 is a spindle pole-associated scaffold protein with pleiotropic functions during corticogenesis. Recessive mutations in WDR62 are associated with structural brain abnormalities and account for the second most common cause of autosomal recessive primary microcephaly (MCPH), indicating WDR62 as a critical hub for human brain development. Here, we investigated a C-terminal truncating mutation (D955AfsX112) in WDR62 using induced pluripotent stem cells (iPSCs) obtained from a patient with MCPH2. We generated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Human induced pluripotent stem cells (hiPSCs) provide a promising alternative, allowing the creation of SCZ patient-specific disease models to explore cellular and molecular phenotypes (Angulo Salavarria et al, 2023). Indeed, hiPSCs enable the generation of various brain-specific cell types, including cortical neurons, interneurons, astrocytes, and microglia (Abud et al, 2017; Muffat et al, 2016; Dell’Amico et al 2023). Several studies identified impaired neuronal maturation, reduction of neurite length and outgrowth through these cellular populations, along with an excitatory-inhibitory imbalance, including enhanced GABAergic-related neuronal expression and genetic upregulation (Brennand et al, 2011; Park et al, 2020; Sawada et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Human induced pluripotent stem cells (hiPSCs) provide a promising alternative, allowing the creation of SCZ patient-specific disease models to explore cellular and molecular phenotypes (Angulo Salavarria et al, 2023). Indeed, hiPSCs enable the generation of various brain-specific cell types, including cortical neurons, interneurons, astrocytes, and microglia (Abud et al, 2017; Muffat et al, 2016; Dell’Amico et al 2023). Several studies identified impaired neuronal maturation, reduction of neurite length and outgrowth through these cellular populations, along with an excitatory-inhibitory imbalance, including enhanced GABAergic-related neuronal expression and genetic upregulation (Brennand et al, 2011; Park et al, 2020; Sawada et al, 2020).…”
Section: Introductionmentioning
confidence: 99%